Objective Characteristics of Accommodation in Present-Day Schoolchildren with Different Levels of Myopia (Global Journal of Medical Research, 2022)
Purpose We study the state of the accommodative function in present-day schoolchildren using the method of computer accomodography Patients and methods 74 children 10 16 years old 54 of them with different degrees of myopia and 20 children control group with emmetropia were tested on the computer accomodography devise Righton Speedy-K ver MF-1 The strength of the accommodative response accorded to the presented accommodative stimulus was determined by calculating the accommodative coefficient response CAO and the contraction s nature of the ciliary body fibers by determining the microfluctuation coefficient KMF
Keywords: accommodation; computer accommodation; accommodative microfluctuations; myopia